Recitation of Seurembek, psychological well-being, and community resilience from the perspective of positive psychology - Abdul Rahman Shaleh; Samsul Bahri; Muhammad Nuzul Abraar; Ali Abdurahman Simangunsong; Salwa Mahalle (Psikohumaniora: Jurnal Penelitian Psikologi, 2025)
The Seurembek tradition is a collective Qur’an recitation practice with deep spiritual and social meaning for the local Muslim community in Pidie Regency, Aceh. This practice not only functions as a form of worship but also as a space for social interaction that strengthens community ties and provides meaning to life for its practitioners. This study aims to examine the contribution of the Seurembek tradition to individual psychological well-being and community resilience through a positive psychology framework. A descriptive, qualitative approach was employed, with data collection conducted through in-depth interviews, participatory observation, and Focus Group Discussions (FGDs) involving Seurembek practitioners, religious leaders, and local community members. The research findings indicate that Seurembek strengthens several dimensions of psychological well-being, including providing meaning and purpose in life, increasing positive emotions, and fostering intense social connectedness. In addition, this practice plays an essential role in strengthening community resilience to various social and spiritual pressures by fostering solidarity, social cohesion, and collective coping mechanisms rooted in religious and cultural values. This finding confirms that preserving the Seurembek tradition has strategic value for improving mental health and social resilience, grounded in local wisdom. The implications of this research open opportunities to develop contextual and culturally oriented positive psychology interventions for Muslim communities in Indonesia.